Mesenchymal Stem Cell in 3D Culture: Diminishing Cell Senescence in Cryopreservation and Long-term Expansion - Jundan, Sheila Fawziyya; Amalia, Riezki; Sartika, Cynthia Retna (Molecular and Cellular Biomedical Sciences, 2023)
Mesenchymal stem cells (MSCs) are widely recognized in cell treatment due to their capacity to secrete trophic factors, differentiate multipotent, and self-renew. Although there is growing evidence that MSCs have therapeutic benefits in various clinical settings, these cells eventually lose their ability to regenerate as they age, which increases cellular dysfunction. Several factors may affect MSCs aging, such as culture dimensions, cryopreservation process, and long-term expansion. Traditional two-dimensional (2D) culture conditions lack the complexities required to recreate MSCs in their natural environment. Meanwhile, three-dimensional (3D) culture mimics the niche, dynamic, and specialized microenvironments of the cells in vivo. The most used storage technique for MSCs, cryopreservation, requires a very low temperature reduction, which stresses cells and can cause the release of pro-inflammatory cytokines. For the utilization of MSCs in therapeutic applications, an in vitro expansion technique is required. Repeated expansion may reduce proliferative capacity, disrupts cellular shape, and impairs the somatic cell function of MSCs. Various processes and techniques may influence MSCs leading to cell aging. One of the culture methods, 3D culture, is shown to reduce the factors that will compromise the therapeutic effects of MSCs, especially cell senescence. The effect of culture dimensions, cryopreservation, and long-term expansion on cell senescence will be discussed in this review article.Keywords: cell aging, mesenchymal stem cell, 3D culture, cell senescence, cryopreservation, long-term expansion